A Review: Analysis of Betacyanin Levels in Various Natural Products - Halimfanezi, Larra; Asra, Rusdi Ridho (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Betacyanin is a pigment that can be used as a natural pigment for food and as an alternative to synthetic dyes because it has an attractive color. Other than that, it also dissolves easily in water, and has high antioxidant activity so it is safer for the body when consumed. The purpose of this article is to discuss the levels of betacyanin in various natural products that can be analyzed using methods UV-Vis Spectrotometer, HPLC. Data Sources Study Selection: The review method used is by studying the literature relevant to the research. Data sources of this article were selectively taken from Google Schoolar, Pubmed, Science Direct, Researchgate and Mandeley. Summary of contents of the article: Betacyanin is one of the most widely used natural dyes in food. Betacyanin is a pigment that functions to provide a red color and has the potential to be a natural dye for food that is safer for health than synthetic dyes. Betacyanin is found in plants such as in red dragon fruit (Hylocereus polyrhiyus), beets (Beta vulgaris L.), cactus fruit (Opuntia elatior Mill.), and in Inflorescence Celosia. The level analysis was carried out in various types of plants that were known to contain betacyanin, the most common method used in analyzing the levels of betacyanin was using a UV-Vis spectrofotometer and HPLC with the results of the study showing that the observed betacyanin had a maximum wavelength of 538 nm. Conclusion: Betacyanin is of betalain pigments which can be used as a natural dye alternative to synthetic dyes. The analysis of betacyanin levels was tested in various plants. Betacyanin has a sligtly different levels in various natural products that has been widely analyzing using the UV-Vis spectrofotometer and HPLC methods.